Telerehabilitation in Scotland: Current Initiatives and Recommendations for Future Development - Anne Hill (International Journal of Telerehabilitation)
Rehabilitation services are set to become central to modern health care systems as they strive to support an increasingly ageing population to live as independently as possible, while maintaining quality services. Alternative service delivery options such as telerehabilitation may assist in meeting the growing demand for services and many countries are exploring the potential use of telerehabilitation within their health care systems. The Scottish Centre for Telehealth commissioned an independent scoping study and subsequent report into the potential development and realisation of telerehabilitation services across Scotland. The scope of the report was restricted to adult rehabilitation services and aimed to identify opportunities for the use of telerehabilitation and to recommend clear and achievable steps towards implementation of telerehabilitation. This article outlines some of the telerehabilitation initiatives currently underway in Scotland and discusses some of the key recommendations made in the report to the Scottish Centre for Telehealth for the future advancement and application of telerehabilitation across Scotland.